1980
DOI: 10.2105/ajph.70.3.284
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between carboxyhemoglobin and serum thiocyanate determinations as indicators of cigarette smoking.

Abstract: Cigarette smoking histories were compared to carboxyhemoglobin and serum thiocyanate concentrations obtained from 426 smokers and 191 non-smokers. The mean levels of both carboxyhemoglobin and serum thiocyanate were significantly higher among cigarette smokers and correlated with the number of cigarettes smoked per day. The specificity of both procedures was 81 per cent, and serum thiocyanate had a higher sensitivity (93 per cent vs. 83 per cent), making it potentially more suitable for use as an index of ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 12 publications
2
16
1
Order By: Relevance
“…Similar increase of the SCN concentration in serum of normotensive and hypertensive pregnant women compared to nonsmokers was reported by Kosanović et al (2007). The results of this study related to higher levels of COHb and SCN in rats exposed to nontreated tobacco smoke are also in agreement with the study of Cohen et al (1980) who reported such results in 191 non-smokers and 426 cigarette smokers.…”
supporting
confidence: 92%
“…Similar increase of the SCN concentration in serum of normotensive and hypertensive pregnant women compared to nonsmokers was reported by Kosanović et al (2007). The results of this study related to higher levels of COHb and SCN in rats exposed to nontreated tobacco smoke are also in agreement with the study of Cohen et al (1980) who reported such results in 191 non-smokers and 426 cigarette smokers.…”
supporting
confidence: 92%
“…The mean COHb in our study group was 3.35% (±1.73). Our results showed that COHb levels among nonsmokers and smokers who smoked up to 10 cigarettes per day and 11-19 cigarettes per day were higher than those reported by Cohen and Bartsch [16], Smoking is implicated as a major contributing factor to the elevation of COHb among clean ers. A number of studies have suggested that cigarette smoking reduces working capacity in direct relation to the level of COHb present in the working person [1,2,11], In this study, the maximal working capacity was signifi cantly impaired (p < 0.05) among those sub jects who smoked 20 cigarettes per day or more; the difference ranged between 23 and 40%.…”
Section: Discussioncontrasting
confidence: 60%
“…The false negative and false positive rates for the DETB extraction method in identifying smokers and non-smokers--namely, zero and 3% respectively-compare very favourably with the published results of other tests. False negative rates of 12-34% have been found when expired carbon monoxide was used for identification, 5-17% with blood carboxyhaemoglobin, 7-36% with serum or plasma thiocyanate, 5% for plasma continine, and 28% with a combination of serum thiocyanate and expired carbon monoxide.34 [17][18][19][20][21][22] The corresponding proportions of false positives in these studies were 1-5%, 0-19%, 2%, and 1% respectively.…”
Section: Dwussionmentioning
confidence: 75%